Crytallization and high-resolution X-ray diffraction data collection of an Asp49 PLA(2) from Bothrops jararacussu venom both in the presence and absence of Ca2+ ions - Murakami, M. T.; Michelan-Duarte, S.; Cintra, ACO; Arni, R. K. (Elsevier B.V., 2004)
Snake venom PLA(2)s have been extensively studied due to their role in mediating and disrupting physiological processes such as coagulation, platelet aggregation and myotoxicity. The Ca2+ ion bound to the putative calcium-binding loop is essential for hydrolytic activity. We report the crystallization in the presence and absence of Ca2+ and X-ray diffraction data collection at 1.60 Angstrom (with Ca2+) and 1.36 Angstrom (without Ca2+) of an Asp49 PLA(2) from Bothrops jararacussu venom. The crystals belong to orthorhombic space group C222(1). Initial refinement and electron density analysis indicate significant conformational. changes upon Ca2+ binding. (C) 2004 Elsevier B.V. All fights reserved.
Keywords: calcium-binding loop; Asp49 PLA(2); crystallization; X-ray diffraction